2017
DOI: 10.4314/ijbcs.v10i6.19
|View full text |Cite
|
Sign up to set email alerts
|

Perception de risques du paludisme et utilisation des moustiquaires au Tchad

Abstract: Perception of malaria risk and use of bed nets in Chad ABSTRACTThe use of Long Lasting Insecticidal-treated Nets (LLINs) and the seasonal malaria chemoprevention are efficient strategies in the fight against malaria. The objective of this survey is to assess the community knowledge about malaria and LLIN use. A descriptive households' survey has been conducted in Chad using questionnaires targeting the head of households. Data collected were entered in Access 2007, cleaned and validated during a workshop held … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
3
0
3
Order By: Relevance
“…Regarding the use of mosquito nets, 58.4% of the survey respondents reported having slept under mosquito net the night before the survey, which is high considering the period of the study (dry season). Other studies in Chad have found also a comparative percentage of 60.1% [ 1 ], 37.6% [ 49 ] and 31.7% [ 47 ]. As found elsewhere [ 50 , 51 ] high usage of nets can be explained by a perception that nets prevent insects bites rather than malaria.…”
Section: Discussionmentioning
confidence: 94%
“…Regarding the use of mosquito nets, 58.4% of the survey respondents reported having slept under mosquito net the night before the survey, which is high considering the period of the study (dry season). Other studies in Chad have found also a comparative percentage of 60.1% [ 1 ], 37.6% [ 49 ] and 31.7% [ 47 ]. As found elsewhere [ 50 , 51 ] high usage of nets can be explained by a perception that nets prevent insects bites rather than malaria.…”
Section: Discussionmentioning
confidence: 94%
“…Suivant le niveau d'instruction, les sujets étaient en majorité non scolarisés (70%). Ce résultat confirme celui de Yandaï et al (2017) au Tchad, qui avait une fréquence de non scolarisation de 62,4% chez les pères et 71,3% chez les mères. Pareillement, un taux de non scolarisation de 70,5% fut observé au Tchad par le Ministère de la Santé Publique (MSP Tchad, 2013).…”
Section: Discussionunclassified
“…Quant à la possession de MI, nous avons rapporté un pourcentage de 68%. Une pareille enquête fut réalisée au Mali par le PNLP (2010) ainsi que par Yandaï et al (2017) au Tchad. Ces auteurs précités ont rapporté respectivement un taux de possession de MI de 85% et 80,6%.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…This could be explained by a lack of documented data on knowledge, attitutes and practices of rabies in communities. However, many studied have indicated the relevance of stakeholders awareness in diseases prevention and control (Fusi Ngwa et al, 2010 ;Yandaï et al, 2017). To address this gap, our study was conducted in five urban and rural health districts with the aim of decribing the knowledge, attitudes and practices of people regarding rabies and its prevention and control.…”
Section: Introductionmentioning
confidence: 99%